Tin oxide composition and preparation method thereof, modified tin oxide ceramic target material and preparation method thereof
By doping high-valent metal ions into the tin oxide lattice to form donor energy levels and using liquid-phase sintering additives with high-valent metal ions, the problem of increased resistivity of tin oxide ceramic targets is solved, and the excellent characteristics of low resistivity and high density are achieved, which are suitable for a variety of electronic and optoelectronic applications.
Patent Information
- Application Number
- CN202510054577.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-14
AI Technical Summary
In practical applications, tin oxide still faces problems such as further reduction in resistivity and improvement in density. The existing doping methods have the problem of canceling n-type and p-type doping, resulting in an increase in resistivity.
The donor energy level is formed by doping high-valent metal ions of +5 or +6 valent to the tin oxide lattice to replace the Sn ions, free electrons are generated, carrier concentration is increased, and resistivity is reduced. At the same time, liquid phase sintering additives of high-valent metal ions (such as Nb2O5 or V2O5) are used to avoid the low-valent sintering additives metal ions entering the lattice to form the main energy level, resulting in an increase in resistivity.
It has achieved low resistivity and high density of tin oxide ceramic targets, and has excellent transparent conductive properties. It is suitable for flat displays and solar cells and other fields.
Smart Images

Figure CN119751044A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oxide target material preparation, and specifically relates to a tin oxide composition and a preparation method thereof, a modified tin oxide ceramic target material and a preparation method thereof. Background Art
[0002] In the field of modern electronics and optoelectronics, transparent conductive oxide films have always been one of the key materials. ITO (indium tin oxide) has long dominated many applications. However, with the continuous development of technology and the growing demand for applications, ITO has gradually exposed some significant limitations. The indium in ITO is a rare and expensive metal. Its resource scarcity and price fluctuations have brought cost pressure and supply instability risks to related industries.
[0003] In this context, tin oxide has attracted widespread attention as a potential substitute. Tin oxide has relatively abundant resource reserves and a relatively stable price, which is conducive to reducing material costs. Moreover, the electrical properties of tin oxide are comparable to those of ITO in some aspects, and even perform better under certain conditions. In recent years, researchers have been continuously committed to optimizing the performance of tin oxide so that it can better meet the requirements of transparent conductive films for various applications. By improving the preparation process, doping modification and other means, the key properties of tin oxide such as conductivity and light transmittance have been significantly improved, making it show great application potential in touch screens, flat panel displays, solar cells and other fields.
[0004] However, tin oxide still faces some technical challenges in practical applications, such as further reducing resistivity and increasing density. For example, Chinese patent CN117105635A uses antimony trioxide to dope tin oxide, where the generated Sb 5+ Entering the tin oxide lattice generates free electrons and provides n-type doping; zinc oxide is used as a liquid phase sintering aid, and Zn partially dissolves into the tin oxide lattice 2+ Will offset Sb 5+ n-type doping increases the resistivity; Chinese patent CN107352996A doping antimony trioxide and copper oxide (Cu 2+ ), there is also the problem of n-type doping and p-type doping canceling each other out, which further leads to an increase in resistivity. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a tin oxide composition and a preparation method thereof, a modified tin oxide ceramic target and a preparation method thereof. The modified tin oxide ceramic target provided by the present invention has excellent properties of low resistivity and high density.
[0006] In order to achieve the above object, the present invention provides the following scheme:
[0007] The invention provides a tin oxide composition, comprising tin oxide and high-valent metal ions doped into the tin oxide crystal lattice; the high-valent metal ions comprise +5-valent metal ions or +6-valent metal ions.
[0008] Preferably, the +5 valent metal ions include Sb 5+ ; The +6 valent metal ions include W 6+ Or Mo 6+ .
[0009] The present invention provides a method for preparing the tin oxide composition described in the above scheme, comprising the following steps:
[0010] Mixing tin oxide, a high-valent metal oxide and water, and sequentially performing first spray granulation and calcination, wherein the high-valent metal ions in the high-valent metal oxide are doped into the tin oxide lattice to obtain the tin oxide composition;
[0011] The high-valent metal ions include +5-valent metal ions or +6-valent metal ions.
[0012] Preferably, the high-valent metal oxide includes Sb 2 O 5 , WO 3 or MoO 3 ; The mass ratio of tin oxide to high-valent metal oxide is (94-99): (0.5-3).
[0013] Preferably, the calcination temperature is 700-1100° C. and the calcination time is 2-6 hours.
[0014] The present invention provides a method for preparing a modified tin oxide ceramic target, comprising the following steps:
[0015] A tin oxide composition, a high-valent metal oxide sintering aid, a dispersant, a defoaming agent, water and a binder are mixed and subjected to a second spray granulation to obtain a spherical powder; the tin oxide composition is the tin oxide composition described in the above scheme or the tin oxide composition prepared by the preparation method described in the above scheme;
[0016] forming the spherical powder to obtain a modified tin oxide ceramic blank;
[0017] The modified tin oxide ceramic green body is subjected to normal pressure sintering, and the high-valent metal ions in the high-valent metal oxide sintering aid are doped into the tin oxide lattice to obtain the modified tin oxide ceramic target; the high-valent metal ions include +5-valent metal ions.
[0018] Preferably, the high-valent metal oxide sintering aid includes Nb 2 O 5 or V 2O 5 ; The mass ratio of the tin oxide and the high-valent metal oxide sintering aid is (94-99): (0.5-3).
[0019] Preferably, the forming includes molding and cold isostatic pressing; the molding pressure is 30-70 MPa; the cold isostatic pressing pressure is 200-300 MPa.
[0020] Preferably, the pressureless sintering includes: first heating to 500-600°C, keeping warm for 2-4 hours; then heating to 1000-1100°C, introducing oxygen, and keeping warm for 4-10 hours; then heating to 1250-1550°C, keeping warm for 6-48 hours, and then cooling.
[0021] The present invention provides a modified tin oxide ceramic target material prepared by the preparation method described in the above scheme, comprising tin oxide and high-valent metal ions doped into the tin oxide lattice; the high-valent metal ions comprise first high-valent metal ions and second high-valent metal ions; the first high-valent metal ions comprise +5-valent metal ions or +6-valent metal ions; the second high-valent metal ions comprise +5-valent metal ions.
[0022] The present invention provides a tin oxide composition, comprising tin oxide and high-valent metal ions doped into the tin oxide lattice; the high-valent metal ions include +5-valent metal ions or +6-valent metal ions. The present invention is to dope +5-valent or +6-valent high-valent metal ions (such as Sb 5+ , W 6+ Or Mo 6+ ) forms donor energy levels to replace Sn ions, generate free electrons, increase carrier concentration, and significantly reduce resistivity.
[0023] The present invention provides a modified tin oxide ceramic target material. The modified tin oxide ceramic target material provided by the present invention is obtained by doping a high-valent metal ion (such as Sb 5+ , W 6+ Or Mo 6+ ) forms donor energy levels to replace Sn ions, generate free electrons, increase carrier concentration, and significantly reduce resistivity. At the same time, the present invention innovatively dopes liquid phase sintering aids with high-valent metal ions (such as Nb 2 O 5 or V 2 O 5 ), successfully avoiding the use of low-valent sintering aid metal ions (such as Cu 2+ 、Zn 2+) partially enters the lattice to form an acceptor energy level and associates with the donor energy level, resulting in an increase in resistivity. In addition, the present invention uses a high-valent sintering aid for doping to form a donor energy level to replace Sn ions, thereby reducing the resistivity of the ceramic target. The preparation method of the present invention is simple, and the modified tin oxide ceramic target prepared by the present invention has the excellent characteristics of low resistivity and high density (i.e., relative density), and has broad application prospects in the fields of flat display and solar cells.
[0024] In the present invention, the formation of high density is mainly due to the role of liquid-phase sintering aids: during the sintering process, the liquid-phase sintering aid forms a liquid phase at high temperature. This liquid phase will wrap around the surface of the solid particles and play a lubricating role, allowing the particles to move and rearrange more easily, thereby promoting densification; liquid-phase sintering aids can improve the material transfer process: during sintering, the atoms or ions in the solid material need to diffuse to achieve the bonding between particles and the filling of pores. The liquid-phase sintering aid can enhance the diffusion of atoms or ions, thereby promoting densification. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0026] Figure 1 This is a cross-sectional scanning electron microscope image of the modified tin oxide ceramic target material of Example 1 of the present invention;
[0027] Figure 2 The XRD patterns of the modified tin oxide ceramic target and the tin oxide raw material used in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The invention provides a tin oxide composition, comprising tin oxide and high-valent metal ions doped into the tin oxide crystal lattice; the high-valent metal ions comprise +5-valent metal ions or +6-valent metal ions.
[0029] In the present invention, the +5 valent metal ions preferably include Sb 5+ The +6 valent metal ions preferably include W 6+ Or Mo 6+ .
[0030] The present invention involves doping +5-valent or +6-valent high-valent metal ions (such as Sb 5+ , W 6+ Or Mo 6+) forms donor energy levels to replace Sn ions, generate free electrons, increase carrier concentration, and significantly reduce resistivity.
[0031] The present invention provides a method for preparing the tin oxide composition described in the above scheme, comprising the following steps:
[0032] Tin oxide, high-valent metal oxide and water are mixed, and first spray granulation and calcination are performed in sequence, and high-valent metal ions in the high-valent metal oxide are doped into the tin oxide lattice to obtain the tin oxide composition; the high-valent metal ions include +5-valent metal ions or +6-valent metal ions.
[0033] In the present invention, the high-valent metal oxide includes Sb 2 O 5 , WO 3 or MoO 3 In the present invention, the mass ratio of tin oxide to high-valent metal oxide is preferably (94-99): (0.5-3). In embodiments of the present invention, the mass ratio may be 94:0.5, 94:3, 94:2, 95.3:2.2, 95.5:2, 95.5:3, 96:2.5, 96:3, 96.3:2.2, 97:1, 97:2, 97:3, 99:0.5, 99:1, 99:2 or 99:3. In the present invention, the volume ratio of the mass of tin oxide to water is preferably (2000-3500) g:3L. In an embodiment of the present invention, it can be 2000g:3L, 2200g:3L, 2400g:3L, 2600g:3L, 2800g:3L, 3000g:3L, 3200g:3L, 3400g:3L or 3500g:3L.
[0034] In the present invention, the high-valent metal ions in the high-valent metal oxide are doped into the tin oxide lattice, and the excess oxygen escapes in the form of oxygen gas.
[0035] In the present invention, the doping amount of the high-valent metal ions in the high-valent metal oxide has the following effects on the product:
[0036] Too little doping - no obvious performance improvement: Too little doping means too few free electrons are generated to effectively change the electrical properties, and the conductivity of tin oxide is not significantly improved.
[0037] Excessive doping - causes lattice distortion: When tin oxide is over-doped, it will cause severe lattice distortion, which will increase the internal stress of the material and increase the risk of cracking; change the phase composition of the material and deteriorate performance: Excessive doping may change the phase composition of tin oxide from a single phase of tin oxide to a two-phase or multi-phase mixture, resulting in performance degradation.
[0038] In the present invention, the mixing of tin oxide, high-valent metal oxide and water preferably includes sand milling; the rotation speed of the sand milling is preferably 1800-2200 r / min, and in the embodiment of the present invention, it can be 1800 r / min, 1900 r / min, 2000 r / min, 2100 r / min, 2150 r / min or 2200 r / min; the particle size of the zirconium oxide grinding balls of the sand milling is preferably 0.2-0.4 mm, and in the embodiment of the present invention, it can be 0.2 mm, 0.3 mm or 0.4 mm. In the present invention, the ball-to-material ratio of the sand milling is preferably (3-7): 1, and in the embodiment of the present invention, it can be 3:1, 4:1, 5:1, 6:1 or 7:1. In the present invention, the particle size of the slurry after the sand milling is preferably ≤0.2 um.
[0039] In the present invention, the inlet air temperature of the first spray granulation is preferably 210-240°C, and in an embodiment of the present invention, it can be specifically 210°C, 215°C, 220°C, 225°C, 230°C, 235°C or 240°C; the outlet air temperature of the first spray granulation is preferably 100-120°C, and in an embodiment of the present invention, it can be specifically 100°C, 105°C, 110°C, 115°C or 120°C.
[0040] In the present invention, the particle size of the spray powder obtained by the first spray granulation is preferably 40-60 μm. In the embodiments of the present invention, the particle size may be 40 μm, 45 μm, 50 μm, 55 μm or 60 μm.
[0041] In the present invention, the calcination temperature is preferably 700-1100°C, and in embodiments of the present invention, it can be 700°C, 800°C, 850°C, 900°C, 950°C, 1000°C or 1100°C; the calcination time is preferably 2-6h, and in embodiments of the present invention, it can be 2h, 3h, 3.5h, 4h, 4.5h, 5h or 6h.
[0042] The present invention removes impurities by calcination: in the preparation process of modified tin oxide ceramic target material, the raw materials often contain organic impurities, and calcination can remove these organic impurities; promotes solid solution reaction: calcination can promote the high-valent metal ions in the high-valent metal oxide to fully dissolve into the tin oxide lattice.
[0043] The present invention provides a method for preparing a modified tin oxide ceramic target, comprising the following steps:
[0044] A tin oxide composition, a high-valent metal oxide sintering aid, a dispersant, a defoamer, water and a binder are mixed and subjected to a second spray granulation to obtain a spherical powder; the tin oxide composition is the tin oxide composition described in the above scheme or the tin oxide composition prepared by the preparation method described in the above scheme;
[0045] forming the spherical powder to obtain a modified tin oxide ceramic blank;
[0046] The modified tin oxide ceramic green body is subjected to normal pressure sintering, and the high-valent metal ions in the high-valent metal oxide sintering aid are doped into the tin oxide lattice to obtain the modified tin oxide ceramic target; the high-valent metal ions include +5-valent metal ions.
[0047] The present invention mixes a tin oxide composition, a high-valent metal oxide sintering aid, a dispersant, a defoaming agent, water and a binder, and performs a second spray granulation to obtain a spherical powder; the tin oxide composition is the tin oxide composition described in the above scheme or is the tin oxide composition prepared by the preparation method described in the above scheme.
[0048] In the present invention, mixing the tin oxide composition, a high-valent metal oxide sintering aid, a dispersant, a defoaming agent, water and a binder preferably includes: mixing the tin oxide composition and the high-valent metal oxide sintering aid, dispersing them with the dispersant and the defoaming agent in water, then sand-grinding them evenly, adding the binder and stirring to form a mixed slurry.
[0049] In the present invention, the high-valent metal oxide sintering aid includes Nb 2 O 5 or V 2 O 5 In the present invention, the mass ratio of tin oxide to high-valent metal oxide sintering aid is (94-99): (0.5-3). In the embodiments of the present invention, the mass ratio can be 94:0.5, 94:3, 94:2, 95.3:2.2, 95.3:2.5, 95.5:1.5, 95.5:2, 96:1, 96:1.5, 96:2.5, 96:2.5, 96:3, 96.3:1.5, 96.3:2.2, 97:1, 97:2, 97:3, 99:0.5, 99:1, 99:2 or 99:3.
[0050] In the present invention, the addition amount of the high-valent metal oxide sintering aid has the following effects on the product:
[0051] Effects of too little addition of high-valent metal oxide sintering aids:
[0052] Poor sintering performance: If too little sintering aid is added, it is difficult to form enough liquid phase to promote particle rearrangement during the sintering process. This is like in the absence of lubricant, the friction between the particles is large and it is difficult to stack tightly, resulting in low density and high porosity of sintered tin oxide ceramics. Too little sintering aid will also make it difficult to lower the sintering temperature, which will not only increase energy consumption, but also lead to a decrease in tin oxide performance, because too high sintering temperature will cause tin oxide decomposition or abnormal grain growth.
[0053] Effects of excessive addition of high-valent metal oxide sintering aids:
[0054] Causing excessive deformation of the product: When too much sintering aid is added, excessive liquid phase will be formed during the sintering process, which may cause excessive flow and deformation of tin oxide during the sintering process, making the shape of the target product difficult to control.
[0055] Changes in the phase composition of tin oxide and deterioration of its properties:
[0056] Excessive sintering aids will change the single phase of tin oxide. Excessive liquid phase may form a continuous phase at the grain boundary after cooling, reducing the bending strength of the tin oxide target. The appearance of these impurities will also interfere with the original electrical properties of tin oxide, thereby deteriorating the performance of tin oxide.
[0057] In the present invention, the dispersant preferably includes polyethylene glycol; the defoamer preferably includes polydimethylsiloxane; and the binder preferably includes polyvinyl alcohol. In the present invention, the mass of the dispersant is preferably 1 to 2.5% of the total mass of the tin oxide composition and the high-valent metal oxide sintering aid. In the embodiments of the present invention, it can be 1%, 1.5%, 2%, 2.2% or 2.5%; the mass of the defoamer is preferably 0.05 to 0.15% of the total mass of the tin oxide composition and the high-valent metal oxide sintering aid. In the embodiments of the present invention, it can be 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.20%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0 % or 0.15%; the mass of the binder is preferably 1-3% of the total mass of the tin oxide composition and the high-valent metal oxide sintering aid, and in embodiments of the present invention, specifically can be 1%, 1.5%, 2%, 2.2%, 2.5% or 3%; the mass of the water is preferably 90-120% of the total mass of the tin oxide composition and the high-valent metal oxide sintering aid, and in embodiments of the present invention, specifically can be 90%, 100%, 105%, 110%, 115% or 120%.
[0058] In the present invention, the rotation speed of the sand mill is preferably 1800-2200 r / min, and in the embodiment of the present invention, it can be 1800 r / min, 1900 r / min, 2000 r / min, 2100 r / min, 2150 r / min or 2200 r / min; the particle size of the zirconium oxide grinding balls of the sand mill is preferably 0.2-0.4 mm, and in the embodiment of the present invention, it can be 0.2 mm, 0.3 mm or 0.4 mm. In the present invention, the ball-to-material ratio of the sand mill is preferably (3-7): 1, and in the embodiment of the present invention, it can be 3:1, 4:1, 5:1, 6:1 or 7:1. In the present invention, the particle size of the slurry after sand milling is preferably ≤0.2 um.
[0059] In the present invention, the inlet air temperature of the second spray granulation is preferably 210-240°C, and in the embodiment of the present invention, it can be 210°C, 215°C, 220°C, 225°C, 230°C, 235°C or 240°C; the outlet air temperature of the second spray granulation is preferably 100-120°C, and in the embodiment of the present invention, it can be 100°C, 105°C, 110°C, 115°C or 120°C. In the present invention, the particle size of the spherical powder is preferably 40-60μm, and in the embodiment of the present invention, it can be 40μm, 45μm, 50μm, 55μm or 60μm.
[0060] After obtaining the spherical powder, the present invention shapes the spherical powder to obtain a modified tin oxide ceramic blank.
[0061] In the present invention, the molding preferably includes molding and cold isostatic pressing. In the present invention, the molding pressure is preferably 30-70 MPa, and in an embodiment of the present invention, it can be 30 MPa, 40 MPa, 50 MPa, 60 MPa or 70 MPa. In the present invention, the cold isostatic pressing pressure is preferably 200-300 MPa, and in an embodiment of the present invention, it can be 200 MPa, 210 MPa, 220 MPa, 230 MPa, 240 MPa, 250 MPa, 260 MPa, 270 MPa, 280 MPa, 290 MPa or 300 MPa.
[0062] In the present invention, compression molding has the function of forming: compression molding is a commonly used forming process, which is mainly used to press loose powdery materials into products with a certain shape and dimensional accuracy in a mold.
[0063] The influence of the molding pressure: the greater the pressure, the closer the distance between the material particles, and the higher the density of the product; when the pressure is small, the material may not be fully compacted, resulting in more pores inside the product and lower density; but too high a pressure may also cause some problems, such as rupture of brittle materials, because excessive pressure will cause the stress generated inside the material to exceed its tolerance limit. Therefore, the present invention controls the molding pressure to 30-70MPa.
[0064] Cold isostatic pressing can further eliminate internal defects: Cold isostatic pressing can further compact the green body, reduce the internal porosity generated during compression molding, make the material particles fit better, reduce internal porosity and stress concentration, improve the quality of the green body, and facilitate subsequent sintering densification.
[0065] Influence of cold isostatic pressing pressure: Increasing the cold isostatic pressing pressure can significantly increase the density of the material and better ensure the uniformity of the material density; under lower pressure, there may still be some local uncompacted areas inside the material, and after increasing the pressure, these areas can be more fully compacted; appropriately increasing the cold isostatic pressing pressure can make the material particles more tightly bonded and promote subsequent processing such as sintering of the material. Therefore, the present invention controls the cold isostatic pressing pressure to 200-300MPa.
[0066] After obtaining the modified tin oxide ceramic green body, the present invention performs normal pressure sintering on the modified tin oxide ceramic green body, and dopes the high-valent metal ions in the high-valent metal oxide sintering aid into the tin oxide lattice to obtain the modified tin oxide ceramic target; the high-valent metal ions include +5-valent metal ions.
[0067] In the present invention, the +5 valent metal ions preferably include Nb 5+ or V 5+ .
[0068] In the present invention, the pressureless sintering preferably includes: first heating to 500-600°C, keeping warm for 2-4 hours; then heating to 1000-1100°C, introducing oxygen, keeping warm for 4-10 hours; then heating to 1250-1550°C, keeping warm for 6-48 hours, and then cooling. In the present invention, the flow rate of oxygen is preferably 1L / min.
[0069] In the present invention, the first temperature rise is preferably from room temperature to 500-600°C, and in the embodiment of the present invention, it can be 500°C, 520°C, 540°C, 560°C, 580°C or 600°C; the insulation time of the first temperature rise is preferably 2-4h, and in the embodiment of the present invention, it can be 2h, 3h, 3.5h or 4h. In the present invention, the second temperature rise to 1000-1100°C and oxygen is introduced, and in the embodiment of the present invention, it can be 1000°C, 1050°C, 1080°C or 1100°C; the insulation time of the second temperature rise is preferably 4-10h, and in the embodiment of the present invention, it can be 4h, 5h, 6h, 7h, 8h, 9h or 10h. In the present invention, the third heating is to 1250-1550°C. In an embodiment of the present invention, it can be 1250°C, 1300°C, 1350°C, 1400°C, 1450°C or 1500°C. The insulation time of the third heating is preferably 6-48h. In an embodiment of the present invention, it can be 6h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h, 50h or 60h.
[0070] In the present invention, the first heating rate is preferably 3-4°C / min, and in the embodiment of the present invention, it can be 3°C / min, 3.5°C / min or 4°C / min; the second heating rate is preferably 3-4°C / min, and in the embodiment of the present invention, it can be 3°C / min, 3.5°C / min or 4°C / min; the third heating rate is preferably 0.5-2°C / min, and in the embodiment of the present invention, it can be 0.5°C / min, 1°C / min or 2°C / min; the cooling rate is preferably 1-2°C / min, and in the embodiment of the present invention, it can be 1°C / min, 1.5°C / min or 2°C / min. In the present invention, the cooling is preferably to room temperature.
[0071] The present invention adopts the above-mentioned pressureless sintering procedure to have the following advantages:
[0072] Changes in the first heating stage: Particle rearrangement occurs: After forming, the powder particles are in a relatively loose stacking state. As the temperature rises, the particles begin to move and rearrange, which increases the contact points between the particles and the contact area, creating conditions for subsequent material transfer and sintering reactions.
[0073] Effect: Reduce microcracks: Make organic matter evenly and slowly escape from the green body, and reduce microcracks caused by stress concentration. Improve the air permeability of the green body and ensure the smooth sintering process: With the gradual removal of organic matter, the pore structure of the ceramic green body changes, and the air permeability is improved, which is conducive to the discharge of gas and the transfer of heat during the sintering process, making the sintering process more uniform and sufficient, and improving the sintering quality of the ceramic. More thorough degreasing, maintaining the shape and dimensional accuracy of the green body: The volatilization of organic matter during sintering will cause drastic volume changes in the green body, thereby affecting the shape and dimensional accuracy of the green body. After thorough degreasing, the volume and size changes of the green body are relatively small, and the shape and dimensional accuracy after forming can be better maintained. Improve the density of ceramics: If the organic matter is not completely removed before sintering, the organic matter will decompose and volatilize during high-temperature sintering, producing a large amount of gas. If these gases cannot be discharged in time, pores will be formed in the ceramic green body, reducing the density and mechanical properties of the ceramic.
[0074] Changes in the second heating stage: Neck formation: The atoms at the contact points between the particles move to the contact points through diffusion, resulting in an increase in the material at the contact points, forming the so-called "neck" structure, just like a "neck" connecting the two particles. This is an important sign of the beginning of sintering. The formation of the neck gives the particles a preliminary bond, but the overall body is still relatively loose and the density increase is not obvious. Neck growth: As the temperature continues to rise, the atomic diffusion rate accelerates, the necks between the particles continue to grow, the connection between the particles becomes tighter, and the density of the body gradually increases. This stage is the key stage of body densification and has an important impact on the density and performance of the final ceramic product.
[0075] Changes in the third heating stage: Pore elimination: The material on the grain boundary continues to diffuse into the pores, so that the pores are gradually filled and eliminated, and the density of the green body is further increased, approaching the theoretical density. At this time, most of the pores have been separated into isolated small pores, and the size of these small pores continues to decrease until they finally disappear, making the ceramic material denser. Grain growth: Under high temperature, the grains will continue to grow, and the size and shape of the grains will affect the performance of the ceramic. Generally speaking, ceramic materials with moderate grain size have good mechanical and physical properties, but if the grains grow excessively, it may cause problems such as decreased strength and reduced toughness of the ceramic. Stable performance: After the late sintering process, the structure and performance of the ceramic material gradually stabilize, and performance indicators such as strength, hardness, and density reach a high level, providing a good foundation for the subsequent processing and use of ceramic products.
[0076] In the present invention, the atmospheric pressure sintering has the function of debinding and sintering integration, specifically, it can improve production efficiency: the traditional process is usually debinding first and then sintering, which are two independent processes. The debinding and sintering integration of the present invention combines these two processes together, reducing the turnover time between production links. Due to the reduction of processes, the occupancy time of the equipment is also reduced accordingly. Under the same equipment conditions, the use efficiency of the equipment can be improved and the output can be increased. At the same time, the integrated process can make better use of energy. During the debinding and sintering process, heat can be more effectively utilized, reducing energy consumption and improving production efficiency as a whole. It can ensure product quality: debinding and sintering integration can better control the dimensional accuracy of the product. During the debinding process, the binder in the green body is removed, and the volume of the green body will shrink to a certain extent. If debinding and sintering are carried out separately, the green body may be affected by external factors during the handling and reheating process after debinding, resulting in uneven dimensional changes. The integrated process makes the green body more continuous and controllable in the continuous process of debinding and sintering, reducing the dimensional deviation caused by multiple treatments, thereby improving the dimensional accuracy of the product. For the performance of the product, this integrated process is conducive to improving the density and uniformity of the product. In the continuous debinding and sintering process, the pores inside the material can be more effectively controlled and reduced. For example, in the production of ceramic materials, the integrated debinding and sintering can make the ceramic body directly sintered at a suitable temperature and atmosphere after the binder is removed, so that the crystal structure inside the material can grow and densify better, improving the mechanical and physical properties of the product, such as strength, hardness and wear resistance.
[0077] The present invention provides a modified tin oxide ceramic target material prepared by the preparation method described in the above scheme, comprising tin oxide and high-valent metal ions doped into the tin oxide lattice; the high-valent metal ions comprise first high-valent metal ions and second high-valent metal ions; the first high-valent metal ions comprise +5-valent metal ions or +6-valent metal ions; the second high-valent metal ions comprise +5-valent metal ions.
[0078] In the present invention, the +5 valent metal ions in the first high-valent metal ions preferably include Sb 5+ The +6 valent metal ions in the first high-valent metal ion preferably include W 6+ Or Mo 6+ .
[0079] In the present invention, the +5 valent metal ions in the second high-valent metal ions preferably include Nb 5+ or V 5+ .
[0080] In the present invention, the relative density of the modified tin oxide ceramic target material is ≥98%, the volume resistivity is ≤10 mΩ·cm, and the average grain size is ≤10 μm.
[0081] The modified tin oxide ceramic target provided by the present invention is prepared by doping high-valent metal ions (such as Sb 5+ , W 6+ Or Mo 6+ ) forms donor energy levels to replace Sn ions, generate free electrons, increase carrier concentration, and significantly reduce resistivity. At the same time, the present invention innovatively dopes liquid phase sintering aids with high-valent metal ions (such as Nb 2 O 5 or V 2 O 5 ), successfully avoiding the use of low-valent sintering aid metal ions (such as Cu 2+ 、Zn 2+ ) partially enters the lattice to form an acceptor energy level and associates with the donor energy level, resulting in an increase in resistivity. In addition, the present invention uses a high-valent sintering aid for doping to form a donor energy level to replace Sn ions, thereby reducing the resistivity of the ceramic target. The preparation method of the present invention is simple, and the modified tin oxide ceramic target prepared by the present invention has the excellent characteristics of low resistivity and high density (i.e., relative density), and has broad application prospects in the fields of flat display and solar cells.
[0082] In order to further illustrate the present invention, a tin oxide composition and a preparation method thereof, a modified tin oxide ceramic target and a preparation method thereof provided by the present invention are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.
[0083] Example 1
[0084] A method for preparing a modified tin oxide ceramic target, the specific preparation steps are:
[0085] 2865g of tin oxide and 90g of antimony pentoxide were mixed and put into a sand mill with 3L of pure water for sand milling; the speed of the sand mill was 2000r / min, the particle size of the zirconium oxide grinding balls was 0.3mm, the ball-to-material ratio was 4:1, and the sand milling time was 4h; the slurry was spray granulated, wherein the spray granulation air inlet temperature was 220℃ and the air outlet temperature was 105℃, and a spray powder with a particle size of 40μm was obtained; the spray powder was calcined at 900℃ for 4h to obtain 2941g of calcined powder;
[0086] Then, 2941g of calcined powder and 45g of niobium pentoxide were mixed, and then dispersed with 60g of polyethylene glycol and 3g of polydimethylsiloxane in 3L of pure water, and sand-milled evenly in a sand mill; the speed of the sand mill was 2000r / min, the particle size of the zirconium oxide grinding ball was 0.3mm, the ball-to-material ratio was 4:1, and the sand milling time was 4h; 54g of polyvinyl alcohol was added and stirred for 30min to prepare a mixed slurry;
[0087] The mixed slurry is spray granulated to prepare 40 μm spherical powder, wherein the spray granulation air inlet temperature is 220° C. and the air outlet temperature is 105° C.;
[0088] The spherical powder is molded at 40 MPa by a hydraulic press and then cold isostatically pressed at 290 MPa to obtain a modified tin oxide ceramic blank;
[0089] 500g of modified tin oxide ceramic green body was sintered at normal pressure. First, the temperature was increased from room temperature to 550℃ at 2℃ / min and kept for 3h. Then, when the temperature was increased to 1100℃ at 2℃ / min, oxygen was introduced at a flow rate of 1L / min and kept for 6h. Then, the temperature was continued to be increased at 1.5℃ / min until 1450℃, and kept at this temperature for 30h. Then, the temperature was cooled to room temperature at a rate of 1.5℃ / min to obtain a modified tin oxide ceramic target with a relative density of 99.1%, a bulk resistivity of 1.4mΩ·cm, and an average grain size of 1μm.
[0090] Example 2
[0091] A method for preparing a modified tin oxide ceramic target, the specific preparation steps are:
[0092] 2880g of tin oxide and 75g of tungsten oxide were mixed and put into a sand mill with 3L of pure water for sand milling; the sand mill speed was 2000r / min, the particle size of zirconium oxide grinding balls was 0.3mm, the ball-to-material ratio was 5:1, and the sand milling time was 4h; the slurry was spray granulated, wherein the spray granulation air inlet temperature was 230℃ and the air outlet temperature was 105℃, and a spray powder with a particle size of 45μm was obtained; the spray powder was calcined at 800℃ for 5h to obtain 2939g of calcined powder;
[0093] Then, 2939g of calcined powder and 45g of niobium pentoxide were mixed, and then dispersed with 66g of polyethylene glycol and 3g of polydimethylsiloxane in 3L of pure water, and sanded evenly in a sand mill; the speed of the sand mill was 2000r / min, the particle size of the zirconium oxide grinding ball was 0.3mm, the ball-to-material ratio was 5:1, and the sand milling time was 4h; 63g of polyvinyl alcohol was added and stirred for 30min to prepare a mixed slurry;
[0094] The mixed slurry is spray granulated to prepare 45 μm spherical powder, wherein the spray granulation air inlet temperature is 230° C. and the air outlet temperature is 105° C.;
[0095] The spherical powder is molded at 45 MPa by a hydraulic press and then cold isostatically pressed at 280 MPa to obtain a modified tin oxide ceramic blank;
[0096] 500g of modified tin oxide ceramic green body was sintered at normal pressure. First, the temperature was increased from room temperature to 550℃ at 2℃ / min and kept at this temperature for 3h. Then, when the temperature was increased to 1100℃ at 2℃ / min, oxygen was introduced at a flow rate of 1L / min and kept at this temperature for 6h. Then, the temperature was continued to be increased at 1.5℃ / min until 1350℃, and kept at this temperature for 36h. Then, the temperature was cooled to room temperature at a rate of 1.5℃ / min to obtain a modified tin oxide ceramic target with a relative density of 98.7%, a bulk resistivity of 0.9mΩ·cm, and an average grain size of 6μm.
[0097] Example 3
[0098] A method for preparing a modified tin oxide ceramic target, the specific preparation steps are:
[0099] 2859g of tin oxide and 66g of molybdenum oxide were mixed and put into a sand mill with 3L of pure water for sand milling; the sand mill speed was 2000r / min, the particle size of zirconium oxide grinding balls was 0.3mm, the ball-to-material ratio was 6:1, and the sand milling time was 4h; the slurry was spray granulated, wherein the spray granulation air inlet temperature was 240℃ and the air outlet temperature was 105℃, and a spray powder with a particle size of 50μm was obtained; the spray powder was calcined at 1000℃ for 3h to obtain 2909g of calcined powder;
[0100] Then, 2909g of calcined powder and 75g of niobium pentoxide were mixed, and then dispersed with 51g of polyethylene glycol and 3g of polydimethylsiloxane in 3L of pure water, and sanded evenly in a sand mill; the speed of the sand mill was 2000r / min, the particle size of the zirconium oxide grinding ball was 0.3mm, the ball-to-material ratio was 6:1, and the sand milling time was 4h; 57g of polyvinyl alcohol was added and stirred for 30min to prepare a mixed slurry;
[0101] The mixed slurry is spray granulated to prepare 50 μm spherical powder, wherein the spray granulation air inlet temperature is 230° C. and the air outlet temperature is 105° C.;
[0102] The spherical powder is molded at 55 MPa by a hydraulic press and then cold isostatically pressed at 270 MPa to obtain a modified tin oxide ceramic blank;
[0103] 500g of modified tin oxide ceramic green body was sintered at normal pressure. First, the temperature was increased from room temperature to 550℃ at 2℃ / min and kept for 3h. Then, when the temperature was increased to 1100℃ at 2℃ / min, oxygen was introduced at a flow rate of 1L / min and kept for 6h. Then, the temperature was continued to be increased at 1.5℃ / min until 1250℃, and kept at this temperature for 24h. Then, the temperature was cooled to room temperature at a rate of 1.5℃ / min to obtain a modified tin oxide ceramic target with a relative density of 98.3%, a bulk resistivity of 2.8mΩ·cm and an average grain size of 5μm.
[0104] Example 4
[0105] A method for preparing a modified tin oxide ceramic target, the specific preparation steps are:
[0106] 2880g of tin oxide and 90g of antimony pentoxide were mixed and put into a sand mill with 3L of pure water for sand milling; the sand mill speed was 2000r / min, the particle size of zirconium oxide grinding balls was 0.3mm, the ball-to-material ratio was 7:1, and the sand milling time was 4h; the slurry was spray granulated, wherein the spray granulation air inlet temperature was 220℃ and the air outlet temperature was 105℃, and a spray powder with a particle size of 40μm was obtained; the spray powder was calcined at 1100℃ for 2h to obtain 2955g of calcined powder;
[0107] Then, 2955g of calcined powder and 30g of vanadium pentoxide were mixed, and then dispersed with 60g of polyethylene glycol and 3g of polydimethylsiloxane in 3L of pure water, and sand-milled evenly in a sand mill; the speed of the sand mill was 2000r / min, the particle size of the zirconium oxide grinding ball was 0.3mm, the ball-to-material ratio was 7:1, and the sand milling time was 4h; 48g of polyvinyl alcohol was added and stirred for 30min to prepare a mixed slurry;
[0108] The mixed slurry is spray granulated to prepare 40 μm spherical powder, wherein the spray granulation air inlet temperature is 220° C. and the air outlet temperature is 105° C.;
[0109] The spherical powder is molded at 60 MPa by a hydraulic press and then cold isostatically pressed at 260 MPa to obtain a tin oxide ceramic blank;
[0110] 500g of modified tin oxide ceramic green body was sintered at normal pressure. First, the temperature was increased from room temperature to 550℃ at 2℃ / min and kept for 3h. Then, when the temperature was increased to 1100℃ at 2℃ / min, oxygen was introduced at a flow rate of 1L / min and kept for 6h. Then, the temperature was continued to be increased at 1.5℃ / min to 1550℃, and kept at this temperature for 24h. Then, the temperature was cooled to room temperature at a rate of 1.5℃ / min to obtain a modified tin oxide ceramic target with a relative density of 98.9%, a bulk resistivity of 9.3mΩ·cm and an average grain size of 2μm.
[0111] Example 5
[0112] A method for preparing a modified tin oxide ceramic target, the specific preparation steps are:
[0113] 2880g of tin oxide and 75g of tungsten oxide were mixed and put into a sand mill with 3L of pure water for sand milling; the sand mill speed was 2000r / min, the particle size of zirconium oxide grinding balls was 0.3mm, the ball-to-material ratio was 4:1, and the sand milling time was 4h; the slurry was spray granulated, wherein the spray granulation air inlet temperature was 230℃ and the air outlet temperature was 105℃, and a spray powder with a particle size of 45μm was obtained; the spray powder was calcined at 850℃ for 4.5h to obtain 2938g of calcined powder;
[0114] Then, 2938g of calcined powder and 45g of vanadium pentoxide were mixed, and then dispersed with 69g of polyethylene glycol and 3g of polydimethylsiloxane in 3L of pure water, and sand-milled evenly in a sand mill; the speed of the sand mill was 2000r / min, the particle size of the zirconium oxide grinding ball was 0.3mm, the ball-to-material ratio was 4:1, and the sand milling time was 4h; 55g of polyvinyl alcohol was added and stirred for 30min to prepare a mixed slurry;
[0115] The mixed slurry is spray granulated to prepare 45 μm spherical powder, wherein the spray granulation air inlet temperature is 230° C. and the air outlet temperature is 105° C.;
[0116] The spherical powder is molded at 50 MPa by a hydraulic press and then cold isostatically pressed at 275 MPa to obtain a modified tin oxide ceramic blank;
[0117] 500g of modified tin oxide ceramic green body was sintered at normal pressure. First, the temperature was increased from room temperature to 550℃ at 2℃ / min and kept for 3h. Then, when the temperature was increased to 1100℃ at 2℃ / min, oxygen was introduced at a flow rate of 1L / min and kept for 6h. Then, the temperature was continued to be increased at 1.5℃ / min until 1400℃, and kept at this temperature for 30h. Then, the temperature was cooled to room temperature at a rate of 1.5℃ / min. The cooling rate was 1.5℃ / min to obtain a modified tin oxide ceramic target with a relative density of 99.3%, a bulk resistivity of 7.5mΩ·cm, and an average grain size of 4μm.
[0118] Example 6
[0119] A method for preparing a modified tin oxide ceramic target, the specific preparation steps are:
[0120] 2889g of tin oxide and 66g of molybdenum oxide were mixed and put into a sand mill with 3L of pure water for sand milling; the sand mill speed was 2000r / min, the particle size of zirconium oxide grinding balls was 0.3mm, the ball-to-material ratio was 5:1, and the sand milling time was 4h; the slurry was spray granulated, wherein the spray granulation air inlet temperature was 225℃ and the air outlet temperature was 105℃, and a spray powder with a particle size of 43μm was obtained; the spray powder was calcined at 950℃ for 3.5h to obtain 2940g of calcined powder;
[0121] Then, 2940g of calcined powder and 45g of vanadium pentoxide were mixed, and then dispersed with 53g of polyethylene glycol and 3g of polydimethylsiloxane in 3L of pure water, and sand-milled evenly in a sand mill; the speed of the sand mill was 2000r / min, the particle size of the zirconium oxide grinding ball was 0.3mm, the ball-to-material ratio was 5:1, and the sand milling time was 4h; 62g of polyvinyl alcohol was added and stirred for 30min to prepare a mixed slurry;
[0122] The mixed slurry is spray granulated to prepare 43 μm spherical powder, wherein the spray granulation air inlet temperature is 225° C. and the air outlet temperature is 105° C.;
[0123] The spherical powder is molded at 65 MPa by a hydraulic press and then cold isostatically pressed at 250 MPa to obtain a modified tin oxide ceramic blank;
[0124] 500g of modified tin oxide ceramic green body was sintered at normal pressure. First, the temperature was increased from room temperature to 550℃ at 2℃ / min and kept for 3h. Then, when the temperature was increased to 1100℃ at 2℃ / min, oxygen was introduced at a flow rate of 1L / min and kept for 6h. Then, the temperature was continued to be increased at 1.5℃ / min until 1250℃, and kept at this temperature for 20h. Then, the temperature was cooled to room temperature at a rate of 1.5℃ / min to obtain a modified tin oxide ceramic target with a relative density of 98.1%, a bulk resistivity of 9.6mΩ·cm and an average grain size of 6μm.
[0125] Comparative Example 1
[0126] This comparative example provides a modified tin oxide ceramic target material. The preparation method thereof is different from that of Example 1 in that niobium pentoxide is replaced by zinc oxide.
[0127] Comparative Example 2
[0128] This comparative example provides a modified tin oxide ceramic target material. The preparation method thereof is different from that of Example 1 in that niobium pentoxide is replaced by cobalt trioxide.
[0129] Comparative Example 3
[0130] This comparative example provides a modified tin oxide ceramic target material, and the preparation method thereof is different from that of Example 1, except that niobium pentoxide is replaced by manganese dioxide.
[0131] Comparative Example 4
[0132] This comparative example provides a modified tin oxide ceramic target material, and the preparation method thereof is different from that of Example 1, except that niobium pentoxide is replaced by zirconium dioxide.
[0133] Comparative Example 5
[0134] This comparative example provides a modified tin oxide ceramic target material. The preparation method thereof is different from that of Example 1 in that niobium pentoxide is replaced by titanium dioxide.
[0135] Comparative Example 6
[0136] This comparative example provides a modified tin oxide ceramic target material, and the preparation method thereof is different from that of Example 1, except that niobium pentoxide is replaced by copper oxide.
[0137] Comparative Example 7
[0138] This comparative example provides a modified tin oxide ceramic target material, and the preparation method thereof is different from that of Example 1, except that antimony pentoxide is replaced by cerium dioxide. The performance results of the modified tin oxide ceramic targets in Examples 1 to 6 and Comparative Examples 1 to 7 are statistically shown in Table 1, wherein the bending strength adopts GB / T-6569-2006.
[0139] Table 1 Performance of modified tin oxide ceramic targets of Examples 1 to 6 and Comparative Examples 1 to 6
[0140]
[0141] It can be seen from Table 1 that the modified tin oxide ceramic target prepared by the present invention has high relative density (i.e. high density), low resistivity, and an average grain size of <10 μm. By doping high-valent metal ions (Sb 5+ , W 6+ Or Mo 6+ ) forms donor energy levels to replace Sn ions, greatly reducing the resistivity. Liquid phase sintering aids doped with high-valent metal ions (Nb 2 O 5 or V 2 O 5 ), successfully avoiding the low-valent sintering aid metal ions (such as Cu 2+ 、Zn 2+ ) partially enters the crystal lattice to form acceptor energy levels and associates with donor energy levels, resulting in increased resistivity.
[0142] Structural characterization
[0143] Figure 1 This is a cross-sectional scanning electron microscope image of the modified tin oxide ceramic target material of Example 1 of the present invention. Figure 1 It shows that the modified tin oxide ceramic target material obtained in Example 1 has a small and uniform grain size (average grain size 1 μm), and the scale in the figure is 1.177 μm.
[0144] Figure 2 The XRD patterns of the modified tin oxide ceramic target and the tin oxide raw material used in Example 1 of the present invention. Figure 2 The modified tin oxide ceramic target obtained in Example 1 is different from pure SnO 2 The diffraction peaks of SnO2 are consistent, showing a single rutile structure. Antimony and niobium elements are successfully doped into SnO2. 2 In the structure.
[0145] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A tin oxide composition, characterized in that It comprises tin oxide and high-valent metal ions doped into the tin oxide crystal lattice; the high-valent metal ions comprise +5-valent metal ions or +6-valent metal ions.
2. The tin oxide composition according to claim 1, characterized in that The +5 valent metal ions include Sb 5+ ; The +6 valent metal ions include W 6+ Or Mo 6+ .
3. The method for preparing the tin oxide composition according to claim 1 or 2, characterized in that: The following steps are involved: Mixing tin oxide, a high-valent metal oxide and water, and sequentially performing first spray granulation and calcination, wherein the high-valent metal ions in the high-valent metal oxide are doped into the tin oxide lattice to obtain the tin oxide composition; The high-valent metal ions include +5-valent metal ions or +6-valent metal ions.
4. The preparation method according to claim 3, characterized in that The high-valent metal oxide includes Sb2O5, WO3 or MoO3; the mass ratio of the tin oxide to the high-valent metal oxide is (94-99): (0.5-3).
5. The preparation method according to claim 3 or 4, characterized in that: The calcination temperature is 700-1100° C. and the calcination time is 2-6 hours.
6. A method for preparing a modified tin oxide ceramic target, characterized in that: The following steps are involved: A tin oxide composition, a high-valent metal oxide sintering aid, a dispersant, a defoaming agent, water and a binder are mixed and subjected to a second spray granulation to obtain a spherical powder; the tin oxide composition is the tin oxide composition according to claim 1 or 2 or the tin oxide composition prepared by the preparation method according to any one of claims 3 to 5; forming the spherical powder to obtain a modified tin oxide ceramic blank; The modified tin oxide ceramic green body is subjected to normal pressure sintering, and the high-valent metal ions in the high-valent metal oxide sintering aid are doped into the tin oxide lattice to obtain the modified tin oxide ceramic target; the high-valent metal ions include +5-valent metal ions.
7. The preparation method according to claim 6, characterized in that: The high-valent metal oxide sintering aid comprises Nb2O5 or V2O5; the mass ratio of the tin oxide to the high-valent metal oxide sintering aid is (94-99): (0.5-3).
8. The preparation method according to claim 6 or 7, characterized in that: The molding includes molding and cold isostatic pressing; the molding pressure is 30-70 MPa; the cold isostatic pressing pressure is 200-300 MPa.
9. The preparation method according to claim 6 or 7, characterized in that: The pressureless sintering comprises: first heating to 500-600° C., keeping the temperature for 2-4 hours; then heating to 1000-1100° C., introducing oxygen, keeping the temperature for 4-10 hours; then heating to 1250-1550° C., keeping the temperature for 6-48 hours, and then cooling down.
10. The modified tin oxide ceramic target prepared by the preparation method according to any one of claims 6 to 9, characterized in that: It includes tin oxide and high-valent metal ions doped into the tin oxide lattice; the high-valent metal ions include first high-valent metal ions and second high-valent metal ions; the first high-valent metal ions include +5-valent metal ions or +6-valent metal ions; the second high-valent metal ions include +5-valent metal ions.
Citation Information
Patent Citations
Low-temperature sintering composite microwave medium ceramic and preparation method thereof
CN101265097A
Preparation method of low-resistivity indium tin oxide target material
CN108516821A
Gallium oxide doped tin oxide ceramic target material and preparation method thereof
CN112723875A
Nb-doped tantalum-containing tin oxide target material and preparation method thereof
CN117247274A
Tin oxide-based evaporation target material as well as preparation method and application thereof
CN117865670A